Two-dimensional Shear-Wave Elastography Performance in the Noninvasive Evaluation of Liver Fibrosis in Patients with Chronic Hepatitis B: Comparison with Serum Fibrosis Indexes - Zhuang, Yuan; Ding, Hong; Zhang, Yue; Sun, Huichuan; Xu, Chen; Wang, Wenping (Radiology, 2017)
Purpose To investigate the value of two-dimensional (2D) shear-wave elastography (SWE) in the assessment of hepatic fibrosis in patients with chronic hepatitis B (CHB) and to compare the diagnostic performance of this modality with that of liver fibrosis indexes. Materials and Methods The ethics committee approved this study, and informed consent was obtained. From July 2015 to May 2016, 539 subjects who underwent partial hepatectomy were divided into groups according to the Scheuer system by using a resected liver specimen. All patients were examined with 2D SWE and underwent preoperative serologic testing to measure liver stiffness and values of serum fibrosis models, which were compared with histologic findings. Performance of noninvasive methods was determined for index (304 patients) and validation (155 patients) cohorts by using areas under the receiver operating characteristic curve (AUCs). Results For association with substantial fibrosis (≥S2), severe fibrosis (≥S3), and cirrhosis (S4) in the index cohort, the optimal cutoff values of liver stiffness were 7.6, 9.2, and 10.4 kPa, respectively, and AUC values were 0.97, 0.96, and 0.98, respectively. The 2D SWE findings, aspartate transaminase-to-platelet ratio index (APRI), fibrosis index based on the four factors (FIB-4), King's score, and Forns index significantly correlated with hepatic fibrosis stages (ρ = 0.88, ρ = 0.41, ρ = 0.40, ρ = 0.43 and ρ = 0.45, respectively; P < .05). The AUCs for APRI, FIB-4, King's score, and Forns index were 0.77, 0.73, 0.79, and 0.77, respectively, in the diagnosis of substantial fibrosis and 0.70, 0.71, 0.72, and 0.74, respectively, in the diagnosis of cirrhosis. In the validation cohort, AUCs of noninvasive methods used to assess different fibrosis stages did not significantly differ from those for the index cohort. AUCs of 2D SWE in the diagnosis of substantial fibrosis, severe fibrosis, and cirrhosis were 0.97, 0.97, and 0.98, respectively, which were significantly higher than those in serum models (P < .05). Conclusion The 2D SWE protocol could be used to predict substantial fibrosis, severe fibrosis, and cirrhosis in patients with CHB with notably higher diagnostic accuracy than that attained with serum fibrosis models. RSNA, 2016.